An expert system for the back-up protection of a transmission network [microfilm] - Ang, Kok Gei (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001